Women's Grave Perspective of Hadis - Darsitun, Darsitun; Khariri, Khariri; Darojat, Darojat (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2020)
This article is a study of hadith in the perspective of the science of takhrijul hadith. The choice of the title theme is due to the phenomenon of some Muslims who aggressively campaign forbidden grave pilgrimage for women. Among them there are those who forbid, there are those who forbid, and there are those who allow it. This phenomenon makes the writer interested in exploring the hadiths about the grave pilgrimage for women. And it will be very interesting to study more deeply the perspective of the science of Takhrijul Hadith. The research methodology that I use is descriptive qualitative using a type of library research approach. The results of this study indicate that the hadiths about the grave pilgrimage for women have various editors who have different wurud asbabul so their interpretations need to be compared so that they can be used proportionally and fairly.